Pelatihan Pembuatan Nugget Ayam Dengan Penambahan Wortel Pada Guru Dan Orang Tua Siswa SDN 82 Patte’ne, Kabupaten Maros - Hajrawati, Hajrawati; Sonjaya, Herry; Syawal, Sutomo; Sahiruddin, Sahiruddin; Hamsah, Hamsah; Razak, Andi Nurul Mutiah (Universitas Mataram, 2025)
Children's dietary intake significantly determines their nutritional status and the quality of their subsequent development. Housewives play a critical role in providing healthy and nutritious food for their children and other family members, thus preventing the consumption of unhealthy ready-to-eat foods commonly available outside the home, including in school environments. This training aimed to equip teachers and parents (housewives) of students at SDN 82 Patte’ne, Maros Regency, with knowledge and skills to produce chicken nuggets enriched with carrots. The training method involved a combination of lectures/discussions and hands-on practice, encouraging active participant involvement. Participants demonstrated high enthusiasm during the training, effectively comprehending the lecture materials and mastering the practical process of making carrot-enriched chicken nuggets. This was evidenced by the increase in participants' pre-test scores, which averaged 1.42 (categorized as not yet knowledgeable/skillful), to 2.93 (categorized as knowledgeable/skillful) in the post-test conducted after the training. This training program is expected to stimulate and motivate local communities, particularly housewives, to engage in productive ventures in livestock product processing, thereby contributing to improve both family nutrition and income.